(untitled) (TAMADDUN NURI JURNALI, 2024)
In this article, in the first years of our independence in our country, in addition to the work carried out to improve the broadcasting hours of the daily programs broadcasted through the radio communication system, the variety, relevance, and coverage of the topics of the TV programs, in order to introduce our country to the world, the republican radio also broadcasts in foreign countries. the works carried out to increase the number are explained chronologically.